Synthesis and Postpolymerization Modification of Thermoresponsive Coatings Based on Pentaerythritol Monomethacrylate Surface Analysis, Wettability, and Protein Adsorption - Stetsyshyn, Yurij (Langmuir : the ACS journal of surfaces and colloids, 2015)
Properties of novel temperature-responsive hydroxyl-containing poly(pentaerythritol monomethacrylate) (PPM) coatings, polymerized from oligoperoxide grafted to glass surface premodified with (3-aminopropyl)triethoxysilane, are presented. Molecular composition, chemical state, thickness, and wettability are examined with time of flight-secondary ion mass spectrometry (ToF-SIMS), X-ray photoelectron spectroscopy (XPS), ellipsometry, and contact angle measurements, respectively. Temperature-induced changes in hydrophobicity of grafted PPM brushes are revealed by water contact angle and ellipsometric measurements. Partial postpolymerization modification of hydroxyl groups (maximum a few percent), performed with acetyl chloride or pyromellitic acid chloride, is demonstrated to preserve thermal response of coatings. Adsorption of bovine serum albumin to PPM brushes, observed with fluorescence microscopy, is higher than on glass in contrast to similar hydroxyl-containing layers reported as nonfouling. Enhanced and temperature-controlled protein adsorption is obtained after postpolymerization modification with pyromellitic acid chloride